2017
DOI: 10.18632/oncotarget.19009
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs with prognostic significance in osteosarcoma: a systemic review and meta-analysis

Abstract: IntroductionThis study aimed to elucidate the prognostic value of microRNAs (miRNAs) in patients with osteosarcoma.Materials and MethodsStudies were recruited by searching PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure, and Wanfang data-bases (final search update conducted January 2017). Eligible studies were identified and the quality was assessed using multiple search strategies.ResultsA total of 55 articles that investigated the correlation between miRNA expression and either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…Downregulation of plasma miR-124 expression was a predictive biomarker for prognosis of glioma [10,22]. A large number of previous studies have suggested that miR-124 could be used as a molecular marker for tumor progression in cervical cancer [23,24], breast cancer [12,25,26], lung cancer [27,28], and osteosarcoma [29]. Numerous clinical studies have shown that BRCA is the most common type of breast cancer and has poor prognosis survival, and the pathogenesis of breast cancer involves a variety of factors and genes [4,30].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of plasma miR-124 expression was a predictive biomarker for prognosis of glioma [10,22]. A large number of previous studies have suggested that miR-124 could be used as a molecular marker for tumor progression in cervical cancer [23,24], breast cancer [12,25,26], lung cancer [27,28], and osteosarcoma [29]. Numerous clinical studies have shown that BRCA is the most common type of breast cancer and has poor prognosis survival, and the pathogenesis of breast cancer involves a variety of factors and genes [4,30].…”
Section: Discussionmentioning
confidence: 99%
“…The Rang group's results collectively indicated that miR-542-3p acts as a metastasis suppressor in melanoma [118] and as a tumor suppressor in ovarian cancer by directly targeting CDK14 ) and promoting the proliferation of osteosarcoma cells in vitro [231][232][233]. Furthermore, Haflidadóttir et al reported miR148's dual/opposite role in MITF regulation [84].…”
Section: Mirnamentioning
confidence: 99%
“…In contrast, AIT upregulates miR‐126, which is significantly downregulated in a number of tumor types, such as osteosarcoma for which miR‐126 downregulation often appears as sign of poor prognosis (Cheng et al, 2017). miR‐126 is viewed as a tumor suppressor, notably in digestive system cancers where it downregulates various oncogenes (Hu, Xiong, Chen, Zhu, & Zhou, 2019).…”
Section: Regulation Of Mi‐rnas Expression and Functionmentioning
confidence: 99%